High-performance gold/graphene/germanium photodetector based on a graphene-on-germanium wafer. (20th August 2022) - Jiang, Haiyan; Li, Bo; Wei, Yuning; Feng, Shun; Di, Zengfeng; Xue, Zhongying; Sun, Dongming; Liu, Chi
Abstract: The metal/germanium (Ge) photodetectors have attracted much attention for their potential applications in on-chip optoelectronics. One critical issue is the relatively large dark current due to the limited Schottky potential barrier height of the metal/germanium junction, which is mainly caused by the small bandgap of Ge and the Fermi energy level pinning effect between the metal and Ge. The main technique to solve this problem is to insert a thin interlayer between the metal and Ge. However, so far, the dark current of the photodetectors is still large when using a bulk-material insertion layer, while when using a two-dimensional insertion layer, the area of the insertion layer is too small to support a mass production. Here, we report a gold/graphene/germanium photodetector with a wafer-scale graphene insertion layer using a 4 inch graphene-on-germanium wafer. The insertion layer significantly increases the potential barrier height, leading to a dark current as low as 1.6 mA cm −2, and a responsivity of 1.82 A W −1 which are the best results for metal/Ge photodetectors reported so far. Our work contributes to the mass production of high-performance metal/Ge photodetectors.